Electron beam generation in a low-impedance system - Agafonov, A.V. (Вопросы атомной науки и техники, 2006)
Results of computer simulation of low-energy high-current electron beam generation in a low-impedance system
consisting of plasma-filled diode with a long plasma anode, an auxiliary thermionic cathode, and an explosive
emission cathode are given. The auxiliary cathode is used to form the long plasma anode by means of residual gas
ionization by a low-current low-voltage electron beam (currents of amperes, voltage of hundred volts) in an external
longitudinal magnetic field. The high-current low-energy electron beam (currents of tens kA, voltage of tens kV) is
generated from the explosive emission cathode embedded in prepared plasma. The long plasma anode presents
simultaneously a transport channel providing charge neutralization of high-current beam. Computer simulation is
performed using PIC code KARAT for different geometry and position of auxiliary cathode. Computer results are
compared with experimental data. Work supported by RFBR under grant 05-02-16442. Приведены результаты численных экспериментов по генерации низкоэнергетичного сильноточного
электронного пучка в низкоимпедансной системе, включающей в себя плазмонаполненный диод с
протяженным плазменным анодом, вспомогательный термокатод и взрывоэмиссионный катод.
Слаботочный, низковольтный пучок от вспомогательного катода, находящийся во внешнем продольном
магнитном поле, используется для создания протяженного плазменного анода, одновременно
представляющего собой и канал для транспортировки пучка, посредством ионизации остаточного газа.
Сильноточный электронный пучок (ток до десятка килоампер при напряжении в десятки киловольт)
формируется с взрывоэмиссионного катода, погруженного в предварительно сформированную плазму.
Численное моделирование проведено с помощью PIC-кода КАРАТ для различных геометрий и положений
вспомогательного катода. Работа выполнена при поддержке РФФИ по гранту 05-02-16442. Наведено результати чисельних експериментів по генерації низькоенергетичного потужнострумового електронного пучка в низькоімпедансьній системі, що включає в себе плазмозаповнений діод із протяжним плазмовим анодом, допоміжний термокатод і вибухоемісійний катод. Слабкострумовий, низьковольтний пучок від допоміжного катода, що перебуває в зовнішнім поздовжнім магнітному полі, використається для створення протяжного плазмового анода, що одночасно представляє собою і канал для транспортування пучка, за допомогою іонізації залишкового газу. Потужнострумовий електронний пучок (струм до десятка кілоампер при напрузі в десятки кіловольт) формується із вибухоемісійного катода, зануреного в попередньо сформовану плазму. Чисельне моделювання проведене за допомогою PІС-коду КАРАТ для різних геометрій і положень допоміжного катода. Робота виконана за підтримкою РФФІ по гранту 05-02-16442.